Morphological characterization and correlation of seed, fruit, and seedling of Horsfieldia iryaghedhi - EKASARI, INDRIANI; SAHROMI, SAHROMI; WARDHANI, PUTRI KESUMA (Nusantara Bioscience, 2025)
Abstract. Ekasari I, Sahromi, Wardhani PK. 2025. Morphological characterization and correlation of seed, fruit, and seedling of Horsfieldia iryaghedhi. Nusantara Bioscience 17: 218-225. Horsfieldia iryaghedhi is a critically endangered species from the Myristicaceae family. Examining seed, fruit, and seedling morphology of the species is crucial, as generative propagation remains the only known conservation method. Therefore, this study aimed to determine the morphological characterization of the seed, fruit, and seedling of H. iryaghedhi and to analyse the correlation between seed, fruit, and seedling traits. This study was conducted at the Bogor Botanical Garden, utilizing five plant collections. The examined morphological traits included length, width, and weight of the seed, as well as fruit height, root collar diameter, and the number of leaves for the seedling. The results showed that the length, width, and weight of the fruit were 39.64±2.48 mm, 30.04±1.98 mm, and 20.33±3.60 g, respectively. Overall, the correlation between seed and fruit parameters indicates that one trait influences the other. The low variability in fruit and seed traits, despite being obtained from mother trees of different origins, has implications for the species' genetic diversity. The mean for seedling height is 106.74±32.78 cm, and the mean of collar diameter is 1.27±0.64 mm. Height and root collar diameter seedling traits were found to be closely related in 24-month-old seedlings. Understanding the ecology of seedling growth is essential for developing developmental strategies to conserve biodiversity and restore natural habitats. In conclusion, the variability in fruit and seed traits is exhibited by plants obtained from mother trees of different origins. The trees in the Bogor Botanical Gardens study site are mother trees, and this is extremely important for the future sustainable population of this species.
Keywords: Endangered species, Indonesia, Myristicaceae, plant traits, species conservation